Pengenalan Dasar-Dasar Komputer di SD Inpres 12/79 Bonepute: Penelitian - Andi Tabrani Rasyid; Ninda Julfikarni; Yuniar S.; Nur Syafina; Fitriani; Jumria; Syahrul Arifin; Aldi; Andi Zulhuzaemy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the implementation of computer basics introduction activities in improving digital literacy of students at SD Inpres 12/79 Bonepute. The research method used is a case study method with a qualitative approach. Data collection techniques were carried out through interviews, documentation, and limited observations of basic computer learning activities. Researchers used data analysis stages in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that basic computer introduction activities at SD Inpres 12/79 Bonepute were implemented through several programs, namely, 1) introduction to computer hardware and its functions, 2) introduction to basic software such as operating systems and Microsoft Word applications, 3) introduction to a brief history of computer development, and 4) direct practice of using computers for simple typing. The implementation of this program has a positive impact on improving students' technological skills, where they are starting to get used to using computers as a learning tool, have a basic understanding of the functions of computer devices, and show high enthusiasm in utilizing technology as part of learning activities.